2016
DOI: 10.1182/blood-2016-06-721936
|View full text |Cite
|
Sign up to set email alerts
|

Excellent T-cell reconstitution and survival depend on low ATG exposure after pediatric cord blood transplantation

Abstract: Key Points Immune reconstitution after CBT is excellent provided ATG exposure is low or absent. Individualized dosing, or omission of ATG in selected patients, may increase the chance of survival after CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 40 publications
9
121
1
1
Order By: Relevance
“…T‐cell immune reconstitution has been associated with the use of ATG shortly before or after infusion of CB as ATG will increase the depletion of T cells and prohibit the proliferation of CB 30. The reduction of ATG after CBT could achieve an early CD4+ T‐cell immune reconstitution and no exposure to ATG results in even exceptional immune reconstitution potential, as recently shown 31. NK cells typically recover within the first month after transplant and are therefore one of the first lymphocytes to recover after transplant, regardless of stem‐cell source 32.…”
Section: Discussionmentioning
confidence: 99%
“…T‐cell immune reconstitution has been associated with the use of ATG shortly before or after infusion of CB as ATG will increase the depletion of T cells and prohibit the proliferation of CB 30. The reduction of ATG after CBT could achieve an early CD4+ T‐cell immune reconstitution and no exposure to ATG results in even exceptional immune reconstitution potential, as recently shown 31. NK cells typically recover within the first month after transplant and are therefore one of the first lymphocytes to recover after transplant, regardless of stem‐cell source 32.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, it is possible that the effect and outcomes with ATG are dependent on lymphocyte count at the time of infusion, and it is likely that an individualized approach to ATG dosing and timing could be beneficial to avoiding significant impairment in post-HSCT immune reconstitution. [12][13][14] In one interesting study, the serum from patients who underwent HSCT with ATG showed that subpopulations of T lymphocytes (CD4, CD8) and natural killer cells (CD56) are selected that lose epitopes recognized by ATG, whereas B lymphocytes (CD20) and monocytes (CD14) maintain a homogeneity with respect to epitopes recognized by ATG. 15 How the antisera select for specific subpopulations of lymphocytes is unknown and further complicates our understanding of the mechanism of action as well as the variability of activity of ATG.…”
Section: Not All Atg Formulations Are the Samementioning
confidence: 99%
“…9,13 Another way would be to adjust (or delay) timing of G-CSF treatment to prevent coexposure with ATG. G-CSF treatment might even be abandoned in some patients with residual ATG exposure.…”
Section: Org Frommentioning
confidence: 99%
“…All patients received gut decontamination and Pneumocystis jiroveci prophylaxis according to local protocol as previously described. 13 Patients were treated in highefficiency, positive-pressure, particle-free isolation rooms. All CBT patients received 10 mg/kg granulocyte colony-stimulating factor (G-CSF; Neupogen) from day 17 after HCT until neutrophils were .2000 cells/mL.…”
Section: Patients and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation